Streptococcus constellatus and Prevotella bivia Penile Abscess - Sandhya Nalmas; Eliahu Bishburg; Trini Chan (The Scientific World Journal)
Streptococcus constellatus (S. constellatus) is known to cause abscesses in the oral, genitourinary, and gastrointestinal tracts, frequently in association with anaerobic bacteria. We report a rare case of S. constellatus and Prevotella bivia (P. bivia) causing a penile abscess, which was successfully treated with surgical drainage and antibiotic treatment.